C-shaped extinction curves and lean fuel limits of methane oxy-fuel diffusion flames at different oxygen concentrations. (1st January 2020) - Li, Xing; Zhang, Jing; Huo, Jiepeng; Wang, Xiaohan; Jiang, Liqiao; Zhao, Daiqing
Highlights: The extinction limits of oxy-fuel flame were measured at normal- and micro- gravity. C-shaped extinction curve of oxy-fuel flame was obtained by numerical computation. The lean fuel limit of oxy-fuel flame increases with increasing oxygen concentration. The effect of radiation reabsorption on lean limit of oxy-fuel flame is remarkable. The lean fuel limit of oxy-fuel flame with X O  = 0.4 is higher than that of air flame. Abstract: The extinction characteristics and lean fuel limits of methane oxy-fuel diffusion flames with oxygen mole fractions of 0.35 and 0.4 were numerically studied by using two different radiation models, namely optically thin radiation model (OTM) and discrete ordinates method (DOM). Experimental studies on extinction limits of the oxy-fuel diffusion flames under normal- and micro- gravity conditions were conducted. The results of methane air diffusion flame from present normal-gravity and previous micro-gravity experiments were used for comparison and analysis. C-shaped extinction curves, which consist of the stretch and the radiation extinction branches, were obtained by numerical computations using OTM and DOM for the oxy-fuel diffusion flame. The computational results by using the two different radiation models were compared with the experimental results. The computational lean fuel limit by using the DOM agrees well with the experimental result, while the result by OTM is slightly higher. The primary reason is due the effect of radiation reabsorption, which is not considered in the OTM. The computational and experimental results show that the effects of oxygen concentration of the oxidizer on the combustion region and lean fuel limit of the oxy-fuel diffusion flame are significant. The lean fuel limit of oxy-fuel diffusion flame increases with increasing oxygen concentration. Both computational and experimental results suggest that the lean fuel limit of the methane oxy-fuel diffusion flame with oxygen mole fraction of 0.4 is higher than that of the methane air diffusion flame.